Construction of cold-set Mickering emulsion gel using whey protein assembly particles as oil-water interfacial stabilizer and gelling agent: Phase stability, nonlinear rheology, and tribology - Usman Amin; Chi Kong Yeung; Haotian Zheng (Journal of Dairy Science)
ABSTRACT: In the current study, whey protein fractal assembly (FA) particles were manufactured and used as emulsifying agent to manufacture oil-in-water (o/w) emulsion system, namely FA emulsion. The cold-set gelation behavior of FA emulsion was investigated in terms of gel-phase stability, rheology, and tribology. Fractal assembly particles were prepared by heating whey protein isolate (WPI) solution (90 g·L−1) at 80°C for 24 h. The fractal morphology of FA particles was observed using transmission electron microscopy. The “protein aggregation index” for WPI solution and FA sol was found as (mean ±SD) 4.3% ± 0.6% and 78.2% ± 0.7%, respectively. The FA sol had z-average diameter of 133.16 nm ± 3.59 nm. The WPI and FA dispersion systems had similar isoelectric points (IEP) at ∼pH 4.6. FA particles had higher surface hydrophobicity as compared with WPI. The WPI and FA stabilized emulsions showed similar droplet size distribution, however, the FA emulsion had higher surface charge than the WPI emulsion. The WPI and FA emulsions were then used to fabricate 18 cold-set gels by manipulating pH (4.6, 5.8, and 7.0) and added levels of Ca2+ (0, 5, and 10 mM), in which 9 gels derived from WPI emulsion were used as control samples. The WPI emulsion was not able to form self-supported and phase-stable gel under each gelation condition tested in this work, whereas FA emulsion gels demonstrated a superior syneresis stability. According to the large-amplitude oscillatory shear rheology characterization, FA emulsion gels showed both strain stiffening-softening transition and shear-thinning-thickening transition behaviors depending on the applied strain and oscillatory frequency. Lissajous-Bowditch plots revealed unsteady rheological behavior, ranging from perfect plastic to Bingham plastic depending upon the applied angular frequency. The selected FA emulsion gels demonstrated acceptable lubrication behaviors. These findings indicate that the characterized FA emulsion gels may be used as protein-based texturizers in diversified food matrixes.